The applicability of remote sensing and geodetic methods for studying water bodies on the western White Sea coast ... - Frolova, Natalia; Krasnova, Elena; Fatkhi, Mikhail; Samsonov, Timofey; Sazonov, Alexey; Telegina, Anna; Telegina, Ekaterina (EARSeL eProceedings, 2015)
The article presents the results of field studies carried out by the Department of Land Hydrology, Faculty of Geography, Lomonosov Moscow State University, in the area near the White Sea Biological Station, Moscow State University (Kandalaksha Bay, White Sea) in January, June, and September 2014 and January 2015. The objects of studies were the unique lakes on the White Sea coast at different stages of their isolation and separation from the sea. Geodetic methods were applied to determine the surface elevation of modern lakes. The degree of isolation of the studied water bodies was estimated and used to identify the following types of lakes: those permanently disconnected from the sea, those having such connection periodically, and those having it permanently in the form of daily tidal influence. The decrease in seawater inflow caused by ice cover was estimated with the use of a conductivity data logger. In winter, the study area is difficult to access and to work in; therefore, remote sensing products such ...